Exploring science identity among Jordanian high school students: a case study - Ahmad M. Mahasneh; Ahmad M. Gazo; Mohammad H. Abood; Omar A. Al-Adamat (Institute of Advanced Engineering and Science, 2024)
This study aimed to investigate the validity and reliability of the Arabic version of the science identity scale (SIS) and to explore any differences in levels of science identity due to gender. The study sample comprised 304 male and female high school students who had completed the SIS. To achieve study objectives, exploratory factor analysis and confirmatory factor analysis were used. The results of the exploratory factor analysis showed that four factors explained (40.542%) of total variance. The results of the confirmatory factor analysis indicated a good model fit, and the Cronbach alpha was calculated to be 0.85 for the SIS. Finally, the results revealed statistically significant differences in the level of science identity and its subscales (science performance, science competence, science recognition, and science interest) based on the gender variable, with females scoring higher. The study recommends that teachers utilize the SIS to assess the level of science identity among students and implement teaching practices aimed at enhancing the science identity of secondary school students.